2021
DOI: 10.1108/ssmt-03-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Defect patterns study of pick-and-place machine using automated optical inspection data

Abstract: Purpose This paper aims to study the component pick-and-place (P&P) defect patterns for different root causes based on automated optical inspection data and develop a root cause identification model using machine learning. Design/methodology/approach This study conducts experiments to simulate the P&P machine errors including nozzle size and nozzle pick-up position. The component placement qualities with different errors are inspected. This study uses various machine learning methods to develop a roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…After implementing the two kernel functions, it was found that the SVR-RBF model was more effective for predictions compared to the SVR-Linear model. Cen et al (2022) presented P&P defect patterns for different root causes based on automated optical inspection data and developed a root cause identification model using a machine learning. Carvalho et al (2022) presented a study to determine the minimum force required to pull out a surface mount component from a PCB during the wave soldering process.…”
Section: Related Workmentioning
confidence: 99%
“…After implementing the two kernel functions, it was found that the SVR-RBF model was more effective for predictions compared to the SVR-Linear model. Cen et al (2022) presented P&P defect patterns for different root causes based on automated optical inspection data and developed a root cause identification model using a machine learning. Carvalho et al (2022) presented a study to determine the minimum force required to pull out a surface mount component from a PCB during the wave soldering process.…”
Section: Related Workmentioning
confidence: 99%